The absence of surface D-alanylation, localized on lipoteichoic acid, impacts the Clostridioides difficile way of life and antibiotic resistance - Lacotte, Pierre-Alexandre; Denis-Quanquin, Sandrine; Chatonnat, Eva; Le Bris, Julie; Leparfait, David; Lequeux, Thierry; Martin-Verstraete, Isabelle; Candela, Thomas (Frontiers in Microbiology, 2023)
The dlt operon encodes proteins responsible for the esterification of positively charged D-alanine on the wall teichoic acids and lipoteichoic acids of Gram-positive bacteria. This structural modification of the bacterial anionic surface in several species has been described to alter the physicochemical properties of the cell-wall. In addition, it has been linked to reduced sensibilities to cationic antimicrobial peptides and antibiotics. Here, we studied the D-alanylation of Clostridioides difficile polysaccharides with a complete deletion of the dlt operon in the 630 strain. We first confirmed the role of the dlt operon in D-alanylation. Then, we established the exclusive esterification of D-alanine on C. difficile lipoteichoic acid. Our data also suggest that D-alanylation modifies the cell-wall's properties, affecting the bacterial surface's hydrophobicity, motility, adhesion to biotic and abiotic surfaces, and biofilm formation. In addition, our mutant exhibited increased sensibilities to antibiotics linked to the membrane, especially bacitracin. A specific inhibitor DLT-1 of DltA reduces the Dalanylation rate in C. difficile but the inhibition was not sufficient to decrease the antibiotic resistance against bacitracin and vancomycin. In conclusion, our results suggest the D-alanylation of C. difficile as an interesting target to tackle C. difficile infections.